Pengaruh Hambatan Samping sebagai Akibat Aktivitas Pasar terhadap Tingkat Pelayanan Jalan Perintis Kemerdekaan Makassar - Maulana Sakti; Slamet Trisutomo; Louis Santoso (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2013)
Commercial activity is one activity that can cause a great rise of the movement. Raise of this movement affect the increased volume of traffic and eventually cause a traffic jam. There are two locations that can be direct identified in Jl. Perintis Kemerdekaan that is the road ahead M'Tos and Pasar Mandai. One important factor is the cause of the side friction. This research aims to determine how much influence of side friction to the level of service in Jl. Perintis Kemerdekaan. The variables are discussed in this research consisted of variable side friction consisting of pedestrian, vehicle stops, vehicles exits and entries to roadside and slow vehicles. The second variable is the level of service which consists of traffic volume and road capacity. Last variable is the identification of the geometric characteristics of the road way. The analysis used the analysis of the characteristics of the road, side friction analysis and analysis of the level of service roads. The results of this research is the level of service on the road ahead M'Tos in the category less than ideal due to the high volume of traffic at peak hours and then met with high side friction on average. While on the road ahead Pasar Mandai, service levels are somewhat ideal category so that traffic jam on the roads has not been taken into account.